The Effectiveness of Self-Compassion Cognitive Training on Experiential Avoidance & Cognitive Fusion in Patients with Chronic Pain - Sedigheh Farokhi; Fatemeh Rezaei; Simin Gholamrezaei (پژوهشنامه روانشناسی مثبت, 2018)
One of the health problems is chronic pain which, in addition to the physiological factors of psychological factors, also plays an important role in its continuity. The purpose of this study was to investigate the effectiveness of self-Compassion cognitive training on the experiential avoidance & cognitive fusion in patients with chronic pain. This study was a semi-experimental study with a pre-test, post-test with control group A total of 30 patients with chronic pain referring to Khorramabad health centers were selected by available sampling method , And randomly assigned to two experimental and control groups, Then, 30 questionnaires of acceptance and practice (Bound et al.) And cognitive fusion (Guillanderz et al.) Were completed as pre-test. The experimental group participated in 8 sessions of 1 hour of group counseling and did not receive any interventional control group Both groups completed the questionnaires as follow-up after the end of treatment sessions. Data were analyzed using covariance analysis. The results of this study showed that cognitive dyslexia education reduced the avoidance of cognitive and cognitive fusion and consequently the reduction of chronic pain in the experimental group.